2018
DOI: 10.1111/ajt.14624
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 4 blockade improves survival of murine heart allografts subjected to prolonged cold ischemia

Abstract: Prolonged cold ischemia storage (CIS) is a leading risk factor for poor transplant outcome. Existing strategies strive to minimize ischemia-reperfusion injury in transplanted organs, yet there is a need for novel approaches to improve outcomes of marginal allografts and expand the pool of donor organs suitable for transplantation. Aquaporins (AQPs) are a family of water channels that facilitate homeostasis, tissue injury, and inflammation. We tested whether inhibition of AQP4 improves the survival of fully MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…AQP4 is also found in cardiomyocytes where it has been shown to mediate cardiac edema in mouse models of myocardial infarction (Rutkovskiy et al, 2012;Warth et al, 2007). AER-271 was effective in reducing cardiac edema and improving transplant survival in a mouse cold ischemic storage model of cardiac transplantation (Ayasoufi et al, 2018). These results further demonstrate the utility of AER-271 for the control of cytotoxic edema where AQP4 facilitates water movement.…”
Section: Discussionmentioning
confidence: 63%
“…AQP4 is also found in cardiomyocytes where it has been shown to mediate cardiac edema in mouse models of myocardial infarction (Rutkovskiy et al, 2012;Warth et al, 2007). AER-271 was effective in reducing cardiac edema and improving transplant survival in a mouse cold ischemic storage model of cardiac transplantation (Ayasoufi et al, 2018). These results further demonstrate the utility of AER-271 for the control of cytotoxic edema where AQP4 facilitates water movement.…”
Section: Discussionmentioning
confidence: 63%
“…To test the functions of AQP4 in the immune cells, we used a small molecule AQP4 inhibitor, AER-270, for in vitro studies, or a phosphonate prodrug, AER-271, which is quickly converted into AER-270 in vivo 11,16 . We have previously reported that AQP4 is expressed in T lymphocytes and that treatment with AER-270/271 reduces T cell activation and function.…”
Section: Resultsmentioning
confidence: 99%
“…A small molecule inhibitor of AQP4, AER-270/271 (Aeromics LLC, Cleveland, Ohio) was identified as previously described 11 . Mice were injected with AER-271 (10 mg/kg i.p) every 6 hours for 2 or 5 days for a total of either 8 or 20 injections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations